Public Health in Asia during the COVID-19 Pandemic Global Health Governance, Migrant Labour, and International Health Crises - van der Veere, Anoma; Schneider, Florian; Lo, Catherine (Health, Medicine, and Science in Asia, 2022)
Every nation in Asia has dealt with COVID-19 differently and with varying levels of success in the absence of clear and effective leadership from the WHO. As a result, the WHO's role in Asia as a global health organization is coming under increasing pressure. As its credibility is slowly being eroded by public displays of incompetence and negligence, it has also become an arena of contestation. Moreover, while the pandemic continues to undermine the future of global health governance as a whole, the highly interdependent economies in Asia have exposed the speed with which pandemics can spread, as intensive regional travel and business connections have caused every area in the region to be hit hard. The migrant labor necessary to sustain globalized economies has been strained and the security of international workers is now more precarious than ever, as millions have been left stranded, seen their entry blocked, or have limited access to health services. This volume provides an accessible framework for the understanding the effects of the COVID-19 pandemic in Asia, with a specific emphasis on global governance in health and labor.